Blaming the Moi era: Memories of bad governance among Eastlands residents in Nairobi, Kenya. (August 2020) - Park, Jeong Kyung
In the memories of older generations in Nairobi's impoverished neighbourhoods, the reign of Moi, Kenya's second president, was a depressing time of political oppression, mismanagement of resources, rising insecurity and increasing corruption. The objective of this study is to describe how the older generations remember Moi's leadership and to elucidate the social implications of that historical memory. This article draws on oral testimony collected in Eastlands, an urban space that was once vibrant and well maintained but that deteriorated into a slum-like neighbourhood during the Moi era. 'Bad governance' is often considered a chief cause of backwardness and chronic poverty in Africa. African people often criticize their political elites, accusing them of incompetence, greed and oppression. The sharing of stories about ineffective and unaccountable leadership is a purposeful social action aimed at addressing people's current concerns. Through the public remembrance of the Moi regime's discursive and coercive control, the old-timers of Eastlands, who represent the urban poor, assert their rightful place in the post-independence nation by expressing their enduring frustration with their socio-economic marginalization under atrocious governance. This study demonstrates that remembering the Moi era is a means for them to cultivate a shared understanding of the past and to construct political legitimacy for better future leadership in the present context of increasing inequality and impoverishment.